2022
DOI: 10.3390/ijms232415452
|View full text |Cite
|
Sign up to set email alerts
|

A Novel R2R3-MYB Transcription Factor SbMYB12 Positively Regulates Baicalin Biosynthesis in Scutellaria baicalensis Georgi

Abstract: Scutellaria baicalensis Georgi is an annual herb from the Scutellaria genus that has been extensively used as a traditional medicine for over 2000 years in China. Baicalin and other flavonoids have been identified as the principal bioactive ingredients. The biosynthetic pathway of baicalin in S. baicalensis has been elucidated; however, the specific functions of R2R3-MYB TF, which regulates baicalin synthesis, has not been well characterized in S. baicalensis to date. Here, a S20 R2R3-MYB TF (SbMYB12), which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…SiMYB75 positively regulates the responses to drought, salt, and osmotic stress through an ABA-mediated pathway [83]. TcMYB8 and SbMYB12 can respond to MeJA treatment [84,85], and GlMYB4 and GlMYB88 play important roles in the synthesis of flavonoids mediated using MeJA signaling [86]. In this study, we found that regulatory elements associated with MeJA and ABA were most common in EfMYB; thus, we also analyzed the expression characteristics of the nine EfMYB genes after ABA and MeJA treatments.…”
Section: Discussionmentioning
confidence: 88%
“…SiMYB75 positively regulates the responses to drought, salt, and osmotic stress through an ABA-mediated pathway [83]. TcMYB8 and SbMYB12 can respond to MeJA treatment [84,85], and GlMYB4 and GlMYB88 play important roles in the synthesis of flavonoids mediated using MeJA signaling [86]. In this study, we found that regulatory elements associated with MeJA and ABA were most common in EfMYB; thus, we also analyzed the expression characteristics of the nine EfMYB genes after ABA and MeJA treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Baicalin biosynthesis and accumulation in S. baicalensis are known to be tightly regulated by various internal and external signals, although the underlying mechanisms remain largely unclear ( Wang et al., 2022b ). Among these signals, JA and its derivatives are plant stress hormones that play key roles in regulating flavonoid biosynthesis, root growth, and defense against pathogen infection and insect attack ( Zhu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Sb MYB3, functioning as a positive regulator, was shown to bind to the promoter of Sb FNSII-2, thereby promoting RSF biosynthesis in S. baicalensis [ 22 ]. Sb MYB12, a nuclear-localized transcription activator that binds to the Sb CCL7-4, Sb CHI-2, and Sb F6H-1 promoters, positively regulates the generation of baicalin and wogonoside [ 23 ].…”
Section: Resultsmentioning
confidence: 99%